CLEAN MULTIPLICATIVE HYPERRINGS - Ameri, R.; Kordi, A. (Italian Journal of Pure and Applied Mathematics, 2015)
In this work, we introduce the notation of clean multiplicative hyperrings and we will obtain some properties of them. Also we study some topological concepts to prove some results on clean elements of multiplicative hyperrings.